2014
DOI: 10.1200/jco.2013.52.3381
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations Predict Poor Outcome in Patients With Myelodysplastic Syndrome After Hematopoietic Stem-Cell Transplantation

Abstract: Purpose Recurrently mutated genes in myelodysplastic syndrome (MDS) are pathogenic drivers and powerfully associated with clinical phenotype and prognosis. Whether these types of mutations predict outcome after allogeneic hematopoietic stem-cell transplantation (HSCT) in patients with MDS is not known. Patients and Methods We used massively parallel sequencing to examine tumor samples collected from 87 patients with MDS before HSCT for coding mutations in 40 recurrently mutated MDS genes. Results Mutations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
320
4
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(350 citation statements)
references
References 33 publications
18
320
4
8
Order By: Relevance
“…Besides known risk factors such as remission state or karyotype knowledge about specific somatic mutations will also be incorporated into such stratification algorithms. Potential candidates for this seem to be TP53 mutations, as several analyses indicated a dismal prognosis for MDS patients after allo-SCT [65][66][67][68]. The goal is to identify a patient population with an extraordinary high relapse risk for further studies to test innovative prophylactic strategies after transplant.…”
Section: Prophylactic or Pre-emptive Therapy With Hma?mentioning
confidence: 99%
“…Besides known risk factors such as remission state or karyotype knowledge about specific somatic mutations will also be incorporated into such stratification algorithms. Potential candidates for this seem to be TP53 mutations, as several analyses indicated a dismal prognosis for MDS patients after allo-SCT [65][66][67][68]. The goal is to identify a patient population with an extraordinary high relapse risk for further studies to test innovative prophylactic strategies after transplant.…”
Section: Prophylactic or Pre-emptive Therapy With Hma?mentioning
confidence: 99%
“…IHC is standardized, results are available faster than with NGS and costs are 30 to 50 times less, suggesting that IHC is a good alternative to facilitate management decisions. Since TP53 mutations are one of the most powerful prognostic factors in MDS, 1,3 it is imperative that clinicians have a quick, reliable surrogate tool to rapidly identify such mutations in settings where NGS is not readily available. Triaging patients via IHC results would potentially decrease health care costs while increasing the usefulness of available diagnostic tools to identify driver mutations.…”
mentioning
confidence: 99%
“…TP53 mutations are found in 5-10% of MDS patients, are enriched in patients with isolated del(5q), complex cytogenetics, or MDS with fibrosis (MDS-F), and are associated with an overall worse prognosis. [1][2][3][4][5] Next-generation sequencing (NGS) is a valuable ancillary tool, however, the technology may not be economically feasible for routine community use.…”
mentioning
confidence: 99%
“…We demonstrated that the TET2/TP53 mutation was an independent predictor for inferior survival in patients requiring HMT or SCT. The impact of genetic mutations on survival after SCT for MDS was recently reported by Bejar et al 15 In their multivariate analysis, mutations in TP53 (HR, 4.22; P ⩽ 0.001) and TET2 (HR, 1.68; P = 0.037) were each independently associated with shorter OS. We obtained the same result, and our analyses suggested the need for evaluating the mutational status of at least the TET2 and TP53 genes when considering and designing SCT for MDS.…”
mentioning
confidence: 96%